Gambaran Kinerja Tenaga Pelaksana Eliminasi Filariasis Dalam Pelaksanaan POPM Filariasis di Kabupaten Semarang (Studi di Wilayah Kerja Puskesmas Leyangan) - Princessila Enjelin Girsang; Lintang Dian Saraswati; Praba Ginandjar (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2020)
Mass Drug Administration Filariasis is a program to prevent the transmission of filariasis. Semarang District is one of the endemic areas of filariasis and the Mass Drug Administration filariasis program is being implemented from 2017 to 2021. However, it has not yet reached the target results of mass treatment coverage. Research purpose was to describe the performance of Elimination Personnel in Mass Drug Administration in the work area of Leyangan Health Center. This study used a cross sectional research method. Proportionate random sampling technique was applied to obtain 126 samples of respondents. Data obtained by structure interviews using questionnaires. The results showed that 0.8% of respondents had high knowledge, 4.8% had optimal counseling, and 50% had a good perception of their work. Proportion of respondents thought that optimal health center staff supervision were 28,6%, availability facilities of respondents were adequate 96%, 80.2% of respondents had high motivation when implementing mass treatment, and 36.5% of respondents experienced obstacles when implementing mass treatment. Proportion of respondents with quite optimal work performance in filariasis mass treatment were 99,2%, however there were still many activities that had not done optimally.